2021
DOI: 10.1039/d0ra09518d
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of alkali and alkaline earth metals during the preparation of activated carbon from Zhundong high-alkali coal

Abstract: Schematic of the behaviour of the AAEM transformation process during the preparation of AC from Zhundong high-alkali coal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The water-soluble sodium in coal primarily consisted of simple free sodium salt (mainly NaCl and Na2SO4, NaHCO3, etc.) and hydrated ions (Na•xH2O) [26,27]. In Figure 4b, the concentration of SO 2-4 increased, followed by an initial increase and subsequent decrease in HCO -3 .…”
Section: Mechanism Analysis Of Water-coal Interactionmentioning
confidence: 93%
See 1 more Smart Citation
“…The water-soluble sodium in coal primarily consisted of simple free sodium salt (mainly NaCl and Na2SO4, NaHCO3, etc.) and hydrated ions (Na•xH2O) [26,27]. In Figure 4b, the concentration of SO 2-4 increased, followed by an initial increase and subsequent decrease in HCO -3 .…”
Section: Mechanism Analysis Of Water-coal Interactionmentioning
confidence: 93%
“…Numerous studies have confirmed that clay minerals on coal surfaces generally possess a negative charge, enabling cations such The water-soluble sodium in coal primarily consisted of simple free sodium salt (mainly NaCl and Na 2 SO 4 , NaHCO 3 , etc.) and hydrated ions (Na•xH 2 O) [26,27]. In Figure 4b, the concentration of SO 2− 4 increased, followed by an initial increase and subsequent decrease in HCO − 3 .…”
Section: Mechanism Analysis Of Water-coal Interactionmentioning
confidence: 94%
“…Seperti yang ditemukan pada biokarbon lainnya, karbon ini mengandung berbagai mineral yang diserap selama hidupnya sebagai pohon. Sifat alkalinya (Liang et al, 2021) dapat meningkatkan tingkat pH air minum menjadi air dengan pH yang lebih besar dari tujuh secara alami. Sepotong tongkat binchotan yang dimasukkan ke dalam air untuk konsumsi dapat mengikat klorin dan senyawa pengotor lainnya sambil melepaskan mineral berguna seperti kalsium, magnesium, dan potassium sehingga air menjadi lebih bermanfaat.…”
Section: Gambar 1 Presentasi Pembuatan Kerajinan Tangan Karbon Konduk...unclassified